User Satisfaction on printer materials in Perpustakaan Tun Abdul Razak (PTAR)2 / Dg. Suraini Abd. Lait - Abd. Lait, Dg. Suraini (Faculty of Information Management, 2009)
The purpose of this study was to construct an understanding of user satisfaction on printed materials in Perpustakaan Tun Abdul Razak (PTAR) 2. The data from distributions questionnaires gives insight as to the important of printed materials in students1 learning method. Three elements, adequacy of collections, currency of collections, and relevance of collections, play important role in student's usage of printed materials that leads to either student satisfied or not. The objectives of this study are to identify the types of popular printed reference materials used by students for academic purpose in PTAR 2, to investigate the problems faced by the students in using printed reference materials and to identify the student's satisfaction towards printed materials collection in PTAR 2.